x(x+4)+28=(x-1)(x+8)

Simple and best practice solution for x(x+4)+28=(x-1)(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+4)+28=(x-1)(x+8) equation:


Simplifying
x(x + 4) + 28 = (x + -1)(x + 8)

Reorder the terms:
x(4 + x) + 28 = (x + -1)(x + 8)
(4 * x + x * x) + 28 = (x + -1)(x + 8)
(4x + x2) + 28 = (x + -1)(x + 8)

Reorder the terms:
28 + 4x + x2 = (x + -1)(x + 8)

Reorder the terms:
28 + 4x + x2 = (-1 + x)(x + 8)

Reorder the terms:
28 + 4x + x2 = (-1 + x)(8 + x)

Multiply (-1 + x) * (8 + x)
28 + 4x + x2 = (-1(8 + x) + x(8 + x))
28 + 4x + x2 = ((8 * -1 + x * -1) + x(8 + x))
28 + 4x + x2 = ((-8 + -1x) + x(8 + x))
28 + 4x + x2 = (-8 + -1x + (8 * x + x * x))
28 + 4x + x2 = (-8 + -1x + (8x + x2))

Combine like terms: -1x + 8x = 7x
28 + 4x + x2 = (-8 + 7x + x2)

Add '-1x2' to each side of the equation.
28 + 4x + x2 + -1x2 = -8 + 7x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
28 + 4x + 0 = -8 + 7x + x2 + -1x2
28 + 4x = -8 + 7x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
28 + 4x = -8 + 7x + 0
28 + 4x = -8 + 7x

Solving
28 + 4x = -8 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
28 + 4x + -7x = -8 + 7x + -7x

Combine like terms: 4x + -7x = -3x
28 + -3x = -8 + 7x + -7x

Combine like terms: 7x + -7x = 0
28 + -3x = -8 + 0
28 + -3x = -8

Add '-28' to each side of the equation.
28 + -28 + -3x = -8 + -28

Combine like terms: 28 + -28 = 0
0 + -3x = -8 + -28
-3x = -8 + -28

Combine like terms: -8 + -28 = -36
-3x = -36

Divide each side by '-3'.
x = 12

Simplifying
x = 12

See similar equations:

| 5=6p-1 | | 2x(3x+x^2)-2x^2=136 | | 5=s-6 | | -(x)whenx=8 | | 63x^2-44x=-5x+60 | | j-20=-23 | | -p+4(3p-2)+5= | | (x*5)+21(1-x)=10 | | 16i+z^2=0 | | 123-95=31y-38y | | 36-4x+8=5+5x-1 | | -3(3x-2)+10x-9= | | 123-95=31y-38 | | B-17=(-38) | | 10-3(10-(8+x))=7x-(x-10) | | F(x)=7x^2-37x+5 | | -258=-7(5n-4)-6 | | cosx*cosx*3-sinx*sinx*3=0 | | 3x-5(x-4)=16 | | 6-8x=3x-9 | | t^2-12t+90=0000 | | -x^2-15x+600=0 | | 3.7x+59.8=33-9.7x | | 0.05x+0.07(9000-x)=510 | | x^2-15x+600=0 | | 36=18s | | (2x+10)(2x-7)=342-4x^2 | | z^2=-16i | | .53+.21t=1.09t-.79 | | SQRT(2SQRT(22x+5))=SQRT(5x+4) | | 2+6g=11-3y | | 9x-4+4x-2=7x |

Equations solver categories